Properties of magnesium doped nanocrystalline hydroxyapatite synthesize by mechanochemical method - Adzila, S.; Ramesh, S.; Sopyan, I. (Asian Research Publishing Network, 2016)
The sintering behaviour of Magnesium-doped nanocrystalline hydroxyapatite (MgHA) synthesized by mechanochemical method was investigated over the temperature range of 1000 °C to 1300 °C. The properties were investigated in terms of phase stability, bulk density and Vickers hardness. In the present research, a dry mechanochemical synthesis was successfully employed to synthesis a nanocrystalline MgHA powder without any secondary phases. Lower sintering temperature at 1000 °C produced β-TCP phase in MgHA in all concentrations. Hence, doping Mg2+ into HA has induced the formation of brushite and α-TCP where these phases were averagely increased with Mg2+ concentration. Increasing Mg2+ concentrations have led to the decreased of HA phase and increased the secondary phases. Mg2+ did not significantly improved the density of HA as the density decreased with Mg2+ doping at 1200 °C-1250 °C. However, Mg2+ increased the hardness of HA when sintered from 1000 °C to 1300 °C. The maximum hardness was obtained by 3% MgHA sintered at 1250 °C with 5.47 GPa.